Re-evaluating the environment in developmental evolution - Moczek, Armin P. (Frontiers in Ecology and Evolution, 2015)
This manuscript reviews our growing understanding of the role of environmental conditions in shaping development and developmental evolution. It then discusses how this enhanced understanding increasingly questions our intuitive notions of the environment as separable from - and external to - organisms, as a selective force that is passive rather than generative, and as an external agent that organisms respond to, rather than one that organisms actively modify to suit their responses. Throughout I highlight examples of case studies in evo devo and beyond that - by integrating a revised evaluation of the environment into their research programs - have been able to advance long-standing and critical questions in the biological sciences. I end by summarizing several theoretical frameworks that are already well in place to guide a more systemic re-integration of the role of environmental conditions in evo devo.